Selective depletion of plasma cells in vivo based on the specificity of their secreted antibodies. Issue 2 (12th November 2019) - Cheng, Qingyu; Pelz, Andreas; Taddeo, Adriano; Khodadadi, Laleh; Klotsche, Jens; Hoyer, Bimba F.; Alexander, Tobias; Thiel, Andreas; Burmester, Gerd‐R.; Radbruch, Andreas; Hiepe, Falk
Abstract: Antibody‐mediated diseases affect more than 10% of the human population. For most, no cure is available, particularly when the pathogenic antibodies are secreted by long‐lived plasma cells resistant to conventional immunosuppressive therapies. Current therapeutic approaches target not only the plasma cells that secrete pathogenic antibodies, but also those providing protective antibodies. Here, in a murine model bearing long‐lived plasma cells secreting anti‐OVA and ‐chicken gamma globulin (CGG) antibodies, we describe the first‐time use of an antigen‐antibody (OVA/anti‐CD138 antibody) conjugate for in vivo labeling and selective ablation of plasma cells that secrete antibodies specific for the antigen OVA. The selective depletion also led to a stable reduction of the corresponding serum anti‐OVA antibody levels. In contrast, CGG‐specific plasma cells and circulating anti‐CGG antibody levels remained unchanged. The method described here should enable the development of unique causative treatment strategies for established antibody‐mediated diseases sparing humoral immunity. Abstract : Current therapies targeting plasma cells deplete them regardless their specificity. In this proof‐of‐concept study, injection of OVA/anti‐CD138 antibody‐conjugate results in a selective reduction of OVA‐specific plasma cells and the related serum antibody titers in mice. This concept offers a unique therapeutic approach for (auto)antibody‐mediated diseases sparing the humoral immunity .